Media literacy in schools practice, production and progression - Burn, Andrew (Andrew Nicholas); Durran, James; Sage eBooks (London : Paul Chapman, 2007)
Suitable for English and media teachers and curriculum leaders in secondary schools, this title features case studies which show how digital media work can draw on children's own cultural knowledge. It also shows the benefits of such projects in terms of learning outcomes and increased self-esteem for a range of learners.
Specialized.
Description based on print version record.
Includes bibliographical references, filmography and index.
Keywords: Media literacy -- Study and teaching; Mass media in education; Electronic books